If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2y + 2x + 5y = 0 Reorder the terms: 6x + 2x + -2y + 5y = 0 Combine like terms: 6x + 2x = 8x 8x + -2y + 5y = 0 Combine like terms: -2y + 5y = 3y 8x + 3y = 0 Solving 8x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 8x + 3y + -3y = 0 + -3y Combine like terms: 3y + -3y = 0 8x + 0 = 0 + -3y 8x = 0 + -3y Remove the zero: 8x = -3y Divide each side by '8'. x = -0.375y Simplifying x = -0.375y
| -3u^2+11u+4=0 | | 2x-2y+z=4 | | 5x^3+90x^2+85x=0 | | X^2+X=-70 | | 0.3x+5-3+0.1x=0.2(x-6) | | x+y+z+w=0 | | 0.5(x+6)=4(x-2) | | 0.1(20-10x)=2-(2x+9) | | 2x^2+2x+140=0 | | -300+40=t | | x+1.5x+x+2.5x-8=88 | | 14-2(3p+1)=6(4-2p) | | 0.35x+.05(4-x)=.10(-46) | | 16x+4+23x+2=40 | | 3(z-21)+2(z-2)=13 | | 5x+15+113=4x+8 | | 23x+2+16x+4=40 | | 40x+16x+4=23x+2 | | X^2-9*X+20= | | 3(x+2)-4(3-x)=2x-6 | | n+2-2n=-1 | | c=5b+200forb | | b^2+2b-3= | | 1ox+7=207 | | -4(c-24)=-4c-24 | | 8x+6+7x-3=108 | | -2f+7f=29 | | 2(4x+3)-2=x+20 | | 9x+5=8x-6 | | -27=-7(3b-8) | | 2h-4x=13 | | M+4m=-15 |